Key gene co-expression modules and functional pathways involved in the pathogenesis of Graves' disease. (15th October 2018) - Shao, Xiaoqing; Wang, Bin; Mu, Kaida; Li, Ling; Li, Qian; He, Weiwei; Yao, Qiuming; Jia, Xi; Zhang, Jin-an
Abstract: Graves' disease (GD) is a common autoimmune thyroid disease characterized by positive thyroid stimulating hormone receptor antibody. To better understand its molecular pathogenesis, we adopted the weighted gene co-expression network analysis to reveal co-expression modules of key genes involved in the pathogenesis of GD, protein-protein interaction network analysis to identify the hub genes related to GD development and functional analyses to explore their possible functions. Our results showed that 1) a total of 2667 differentially expressed genes in our microarray study and 16 different gene co-expression modules were associated with GD, and 2) the most significant module was associated with the percentage of macrophages, T follicular helper cells and CD4 + memory T cells and mainly enriched in immune regulation and immune response. Overall, our study reveals several key gene co-expression modules and functional pathways involved in GD, which provides some novel insights into the pathogenesis of GD. Highlights: Several key gene co-expression modules were found to be related to GD. The key module is mainly enriched in immune regulation and immune response. Protein-protein interaction network analysis identified some hub genes related to GD.